Syn-sendimentary tectonics in the Ionian unit during the transition from carbonate to clastic sedimentation - ΠΑΠΑΝΙΚΟΛΑΟΥ, Ι. Δ.; ΛΕΚΚΑΣ, Ε. Λ. (Bulletin of the Geological Society of Greece, 2001)
It is well-known that the sedimentation in the Ionian Unit between the limestones and the flysch succession continued without interruption leading to the formation of relatively thick transitional beds. In this paper, phenomena of syn-sedimentary tectonism are reported for the first time during this grading up from the limestones into the flysch, near the village of Kato Retsina in Mesolongi area. Although, a gradual progression from the limestones to the flysch is also observed, in certain locations there is an abrupt change in the sedimentation. Transitional marly beds are missing and faulting is present. Field evidence indicates that faulting in the area took place during the onset of the flysch deposition. These faults are related to the formation of the graben within the flysch basin and form a characteristic angular shape in the limestone-flysch boundary. As a result, there is a change of dip in the strata towards the boundary involving significant disturbance in the lower members of the flysch succession, where also olistoliths are observed. Similar phenomena have been reported from other geotectonic Units such as Tripoli and Parnassos Units. The latter phenomena are characterized by the transition from neritic carbonate to pelagic clastic sedimentation and partly resulted in immersion, erosion, karstification and emergence so as to receive the flysch sediments. However, the Ionian Unit experienced a pelagic carbonate sedimentation that did not lead to erosion and karstification processes. In that case, the theory of non-deposition is proposed, in a paleoenvironment of steep slopes and strong sea currents. These phenomena depict the influence of the neighboring neritic Gavrovo-Tripolis unit. Overall, the study area is located in tectonic blocks that represent the transition from the neritic platform of Gavrovo to the pelagic Ionian Unit.